Machines and mechanisms - Bandyopadhyay, Sandipan; Kumar, G. Saravan; Ramu, Palaniappan (Narosa Publishing House, 2012)
MACHINES AND MECHANISMS form the backbone of industries, implements in agriculture, space exploration, and various appliances used in our daily lives. This title contains new developments at the core of the science of machines and mechanisms, as well as their applications in various walks of life. The contents represent contributions made by about two hundred researchers, practising engineers, and educators working in the fields of analysis and synthesis of mechanisms, robotics, compliant mechanisms, dynamics and control, design of machines for the industries, rural and agricultural sectors etc. in the 15th National Conference on Machines and Mechanisms (NaCoMM 2011). The variety of topics and the diversity of view-points should make the title significantly interesting to the beginner and expert alike in the general field of design and analysis of machines and mechanisms.